Verbos de situación: paralelismos entre usos espaciales y usos atributivos - Bustos Plaza, Alberto (Dicenda. Estudios de lengua y literatura españolas, 2008)
There is a group of Spanish situation verbs featuring both spatial and copular uses. Two separate groups of homonymic predicative and copular verbs have been traditionally posited in this area. Nevertheless, there is a number of semantic, syntactic, lexical and implicative parallelisms pointing to the fact that spatial structures are reused in the more abstract domain of attrib tion of states. This evidence supports the idea that in fact we are dealing with parallel instantiations of the same verbs.